Depression Scores before and after Electrocompulsive Therapy with Propofol versus Ketamine Anesthesia: A Prospective Observational Study - Alsari, Noor Zuhair; Mubarak, Nawfal Ali; Al-Sabbagh, Aqeel Ibraheem (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Background: Major depressive disorder (MDD) is a severe condition marked by persistent sadness and functional impairment. While electrocompulsive therapy (ECT) is effective for treatment-resistant cases, the comparative effects of propofol and ketamine as anesthetic agents remain unclear. Objective: To compare the effects of propofol and ketamine anesthesia on depression severity in patients undergoing ECT using HDRS scores at multiple time points. Methods: In this prospective observational study, 50 patients with treatment-resistant depression were assigned to receive ECT with either propofol- or ketamine-based anesthesia. Depression severity was measured using HDRS at baseline and 1 week, 1 month, and 3 months post-treatment. Secondary outcomes included relapse rates and additional ECT sessions. Results: Patients receiving ketamine showed significantly greater HDRS reductions at all follow-ups (p<0.05), fewer relapses, and less need for additional ECT sessions compared with those receiving propofol. However, ketamine was associated with higher blood pressure. Conclusions: Ketamine was associated with more robust and sustained improvement in depression scores following ECT than propofol. Further studies are needed to confirm these findings and to investigate other anesthetic options.